EFEKTIVITAS METODE PEER TEACHING TERHADAP SELF EFFICACY DAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X DI SMA NEGERI 8 PANDEGLANG - Nurul Novianti; Jaka Wijaya Kusuma; Maulida Nur (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This research was motivated by the tenth grade students at SMA Negeri 8 Pandeglang who lost their self-efficacy and lack of ability to understand mathematical concepts in mathematics. The purpose of this study is to determine the activities and learning processes using the peer teaching method, as well as to find out how much effective the peer teaching method is on self-efficacy and understanding of mathematical concepts for class X students at SMA Negeri 8 Pandeglang. This research is a descriptive qualitative research. The data collection techniques used were observation, questionnaires, students' mathematical concept understanding ability tests, and interviews, the research design was "one group pretest posttest design". The research instrument used was an observation sheet on learning and student activities in the classroom, self-efficacy questionnaires, interviews with teachers and students, and a concept understanding ability test. The analytical techniques used are observation sheets, questionnaires, teacher and student interviews, and tests of students' mathematical concept understanding abilities. The results of the study stated that the results of the observation sheet on the learning process using the peer teaching method showed an average score of 90.8% with very good criteria, while the results of the student activity observation sheet using the peer teaching method showed an average score of 91.6% with very good criteria. . In addition, the results of the calculation of the student's self-efficacy questionnaire showed an average score of 63.68% with effective criteria. Meanwhile, the results of the students' ability to understand mathematical concepts showed an average score of 73% with effective criteria. So it can be concluded that student activities and the learning process using the peer teaching method are very good to use. In addition, the peer teaching method is also effectively used in learning activities on self-efficacy and students' ability to understand mathematical concepts